Prayers of Old People: Zechariah, Simeon and Anna - Mielcarek, Krzysztof (Verbum Vitae, 2012)
The article presents an analysis of three figures of Lucan version of the infancy narrative: Zechariah (Luc 1,5-23.57-79), Simeon (Luc 2,25-35), and Anna (Luc 2,36-38). There at least two thing that make these people alike: they are all in their old age and they pray to God. Even though the material concerning these personages is not fully comparable, it is possible to capture some similarities in their prayer: historical perspective, eschatological dimension, and universalism. All these three people not only pray to God but also the bear a witness to God.